Motives for Marijuana Use among Heavy-Using High School Students: An Analysis of Structure and Utility of the Comprehensive Marijuana Motives Questionnaire - Blevins, Claire E. (Addict Behav, 2016)
Motives for marijuana use are important predictors of problematic outcomes associated with marijuana use. Most measures, to date, were developed by adapting alcohol motives measures. However, the Comprehensive Marijuana Motives Questionnaire (CMMQ) was created using a bottom-up approach to evaluate twelve distinct motives for use. The CMMQ was developed and validated in a normative college population. As such, no known study has evaluated the factor structure and utility of the CMMQ in a heavy-using, high school student population. The current study utilized a sample of 252 heavy marijuana-using high school students recruited for a combination motivational enhancement/cognitive behavioral intervention. Results from baseline measures indicated that the factor structure of the CMMQ was maintained in this population. Results from multiple regression analyses revealed distinct relationships with measures of negative consequences of use, including indices of marijuana use, marijuana-related problems, self-efficacy, and internalizing and externalizing symptoms. In particular, the coping motive was associated with several negative outcomes, which is consistent with previous marijuana and alcohol motives literature. Results suggest that the CMMQ may be useful in assessing marijuana motives among heavy marijuana-using adolescents.